Axonal Dopamine Receptors Activate Peripheral Spike Initiation in a Stomatogastric Motor Neuron - Bucher, Dirk (J Neurosci, 2003)
We studied the effects of dopamine on the stomatogastric ganglion (STG) of the lobster, Homarus americanus. The two pyloric dilator (PD) neurons are active in the pyloric rhythm, have somata in the STG, and send axons many centimeters to innervate muscles of the stomach. Dopamine application to the stomatogastric nervous system when the PD neurons were rhythmically active evoked additional action potentials during the PD neuron interburst intervals. These action potentials were peripherally generated at a region between the STG and the first bilateral branch, ∼1 cm away from the STG, and traveled antidromically to the neuropil and orthodromically to the pyloric dilator muscles. Focal applications of dopamine to the nerves showed that spikes could be initiated in almost the entire peripheral axon of the PD neurons. Dopamine also evoked spikes in isolated peripheral axons. The concentration threshold for peripheral spike initiation was at or below 10(-)(9)m dopamine. Thus, the peripheral axon can play an important role in shaping the output signaling to the muscles by the motor neuron.